2017
DOI: 10.1111/apa.13764
|View full text |Cite
|
Sign up to set email alerts
|

First‐time success with needle procedures was higher with a warm lidocaine and tetracaine patch than an eutectic mixture of lidocaine and prilocaine cream

Abstract: Accepted ArticleThis article is protected by copyright. All rights reserved. Aim: More than 50% of children report apian during venipuncture or intravenous cannulation and using local anaesthetics before needle procedures can lead to different success rates. This study examined how many needle procedures were successful at the first attempt when children received either a warm lidocaine and tetracaine patch or an eutectic mixture of lidocaine and prilocaine (EMLA) cream. Methods:We conducted this multicentre r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…This study raises the question of whether using LPC in bedridden patients increases attempts to conduct thoracentesis and abdominocentesis compared to patients receiving IL. In a study conducted by Cozzi et al, they showed that the success rate of first attempts in needle procedures was significantly higher in the warm lidocaine-tetracaine patch group than lidocaine-prilocaine cream group (25).…”
Section: Discussionmentioning
confidence: 96%
“…This study raises the question of whether using LPC in bedridden patients increases attempts to conduct thoracentesis and abdominocentesis compared to patients receiving IL. In a study conducted by Cozzi et al, they showed that the success rate of first attempts in needle procedures was significantly higher in the warm lidocaine-tetracaine patch group than lidocaine-prilocaine cream group (25).…”
Section: Discussionmentioning
confidence: 96%
“…A multicentre study compared 339 children who were prepared with Rapydan for 30 minutes or EMLA for 60 minutes before venepuncture or intravenous catheterisation. They reported that the pain scores were more than 4/10 in about 10% of patients in both groups 42 . The authors also reported that the application of the warm lidocaine/tetracaine patch may cause a local burning or pain sensation which the child finds unconfortable 42 …”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…Increased successful intravenous catheterisation was achieved when lidocaine cream was compared to a placebo, 36 a warmed lidocaine/tetracaine patch was compared to EMLA 42 and nitrous oxide was compared to oral midazolam 48 . No difference in successful intravenous cannulation was found when buffered lidocaine was compared to a placebo, 24,27 EMLA, 26 vapocoolant 28 or lidocaine cream 25,29 .…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Também foi utilizada no ensaio de Cozzi et al (2017), onde mostrou-se a eficácia da lidocaína e tetracaína quentes em comparação ao EMLA, obtendo taxa de sucesso maior na primeira tentativa em crianças usando adesivos quentes de lidocaína e tetracaína (92,4%) do que utilizando o creme EMLA (85%). No entanto, ocorreram eventos adversos nos dois grupos, possuindo maior incidência no grupo do adesivo quente (6,4%) do que (3,0%) no grupo do creme EMLA (3,0%), mas é importante ressaltar que foram apenas eventos adversos locais e menores (Cozzi et al, 2017).…”
Section: Métodos Farmacológicosunclassified